Copper-Catalyzed Silylcupration of Activated Alkynes - Vercruysse, Sébastien; Jouvin, Kévin; Riant, Olivier; Evano, Gwilherm (Synthesis, 2016)
A highly efficient catalytic silylcupration of activated alkynes is reported. Upon reaction with silylboronates and methanol in THF at room temperature in the presence of copper(I) fluoride tris(triphenylphosphine), a range of ynamides and propiolates were found to undergo a smooth silylcupration. This reaction, which tolerates various functional groups, affords a straightforward and efficient entry to the corresponding β-silylenamides and -acrylates, which were formed with high levels of regio- and stereoselectivities.
Keywords: copper catalysis; silylcupration; ynamides; propiolates; silylboronates